2010
DOI: 10.1159/000272241
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Proteomics – Differences in Protein Expression between Estrogen Receptor-Positive and -Negative Tumors Identified by Tandem Mass Tag Technology

Abstract: Background: Proteomic analysis has become an effective tool in breast cancer research. In this study, we applied the new gel-free tandem mass tag (TMT) reference method for the first time in breast cancer. Materials and Methods: Proteomic analysis was used to compare 10 estrogen receptor (ER)-positive and 10 ER-negative samples. The results of the proteomic approach were validated by Western blot, immunohistochemistry and gene expression analysis. Results: 17 proteins with significant differences in expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This method is successfully used to screen for novel biomarkers in periodontal disease, colorectal cancer tissue and so on [18,19]. Previous study found that TMT labeling was a powerful tool for breast cancer proteomics to find differences in protein amount between estrogen receptor-positive and estrogen receptor-negative tumors [20]. These indicating that this approach is applicable to quantitative proteomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…This method is successfully used to screen for novel biomarkers in periodontal disease, colorectal cancer tissue and so on [18,19]. Previous study found that TMT labeling was a powerful tool for breast cancer proteomics to find differences in protein amount between estrogen receptor-positive and estrogen receptor-negative tumors [20]. These indicating that this approach is applicable to quantitative proteomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Since we first introduced the concept in 2003, isobaric peptide tagging for shotgun proteomics has become an important technique in quantitative mass spectrometry with a growing number of powerful and far-reaching applications in areas such as biomarker discovery, , temporal regulation of proteome dynamics, drug target identification/validation, spatial proteomics, protein turnover, proteogenomics, and drug/protein interaction studies . While isobaric tagging has established itself as an accurate, reliable, and sensitive quantification and multiplexing technique, there is still demand for increased isobaric multiplexing capacity.…”
mentioning
confidence: 99%
“…Commercially available labeling reagents such as iTRAQ and TMT are activated NHS esters that are easily hydrolyzed once dissolved in solution, and are completely lost labeling activity within a short period. Once vials of these reagents are opened, all of them have to be used in one experiment. Thus, the hydrolysis properties would restrict an experimental design and cause the increased cost in experiments.…”
Section: Resultsmentioning
confidence: 99%
“…There are several approaches based upon mass spectrometry for quantitative proteomics, including label-free, MS1- and MS2-based labeling methods . Isobaric tag labeling methods that belong to MS2-based approaches are widely used. Compared with label-free data dependent analysis (DDA) methods, the analysis time and run-to-run variations in the isobaric labeling are greatly reduced because the labeled peptides from multiple samples are mixed together before the LC–MS/MS assay. The sensitivity of peptide detection is greatly enhanced because the MS/MS signal(s) for a peptide is contributed by multiple samples so that its corresponding signal intensity is strengthened.…”
mentioning
confidence: 99%